DETEKSI KONDISI ORGAN GINJAL DAN LAMBUNG MELALUI IRIS MATA MENGGUNAKAN METODE BACKPROPAGATION NEURAL NETWORK - Fanjie Hidayat; Chairisni Lubis; Agus Budi Dharmawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Iridology is a science based on analysis of signs contained in the network structure of the human body such as iris as a reflection of the health condition. According to the science of iridology, iris eye is an extension of the brain. The organs in the body sends vibrations to the body cells and is recorded in the brain. These recordings can then be viewed through the iris of the eye that relate directly to the brain. This project build software for detection of kidney and stomach conditions through the iris with Backpropagation Neural Network. The first process in this application is looking for feature extraction on the iris image by preprocessing stage. The value from feature extraction will be calculated by Backpropagation Neural Network to find the kidney and stomach conditions,  normal or abnormal from the iris image. The test results reached 94.44% from data in database and 72.22% from the untrained data. Key wordsIridologi, Gray Level Cooccurrence Matrix, Backpropagation Neural Network